Attitudes toward vaccines and their relationship with health literacy among İnönü University students - Erkay Nacar; Gülşen Güneş (Scientific Reports in Medicine, 2026)
Aim: This study aimed to determine attitudes toward vaccination among university students and to examine the relationship between these attitudes and health literacy levels. Methods: The population of this cross-sectional study consisted of students at İnönü University. The minimum sample size was calculated as 295 using PASS 11 software. Data were collected between November and December 2017 using faculty-based cluster sampling and a 47-item questionnaire. The questionnaire included items on sociodemographic characteristics, attitudes toward vaccination, and the Turkish Health Literacy Scale (THLS-32). Data were analyzed statistically, and p